The responsibility towards (of) the combatants - Giraldo Ramírez, Jorge (Estudios de Filosofía, 2008)
This reflection revolves around the problem of the status of non-state combatants in postmodern wars and the behavior of the different sides in this type of war. The attention to these issues comes from what seems to me to be two oversights in contemporary reflection on war: the first is the neglect, if not invisibility, of the combatants on account of a colonization of the war sphere by the war. criminal law, for which the only thing that is taken into account are the figures of the perpetrator and the victim. The second oversight refers to the persistence in normative, political and legal discourses that simply extrapolate the presuppositions of modern political theory that understands political agents only under the attributes of state entities. [Fragment]